MENINGKATKAN AKTIVITAS BELAJAR MATA PELAJARAN IPS MELALUI METODE PEMBELAJARAN THINK PAIR SHARE PADA KELAS VII MTS MANBAUL HIKAM - Mariatun, Ika Lis (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Mambaul Hikam Burneh, Bangkalan Regency. Based on the results of observations in class VII IPS MTS Manbaul hikam, the problem that arises from the learning outcomes is the weakness of students in understanding learning to describe economic actors in the economic system Indonesia. This is evident from the 32 students, the remaining 4 students who were able to get learning outcomes above the KKM and on the other hand only achieved grades below the KKM. So if it is presented that only 12.5 percent get a score of 65 (predetermined KKM), even though to achieve completeness the average score of students must be 85 percent to be able to reach the KKM. Based on the problems above, it is necessary to have a countermeasure in order to achieve an increase in student achievement in learning to explain the material of economic actors in the Indonesian economic system. In this study there were 2 cycles with the overall result that in cycle I, the application of the think pair share method was able to improve student achievement at MTS Manbaul hikam burneh. We can see these results from the differences in cycle 1 and cycle 2, including in cycle 1 student activity has reached 39% and in cycle 2 student activity has increased 86%, from here we can see that the application of the think pair share model has been carried out well.